ALT control, delete: FANCM as an anti-cancer target in Alternative Lengthening of Telomeres. (1st January 2019) - O'Rourke, Julienne J; Bythell-Douglas, Rohan; Dunn, Elyse A; Deans, Andrew J
ABSTRACT: Break-induced replication is a specific type of DNA repair that has a co-opted role in telomere extension by telomerase-negative cancer cells. This Alternative Lengthening of Telomeres (or 'ALT') is required for viability in approximately 10% of all carcinomas, but up to 50% of the soft-tissue derived sarcomas. In several recent studies, we and others demonstrate that expression and activity of FANCM, a DNA translocase protein, is essential for the viability of ALT-associated cancers. Here we provide a summary of how and why FANCM depletion leads to deletion of ALT-controlled cancers, predominantly through a hyper-activation of break-induced replication. We also discuss how FANCM can and has been targeted in cancer cell killing, including potential opportunities in ALT and other genetic backgrounds.